Exploring biomechanical variations in ankle joint injuries among Latin dancers with different stance patterns: utilizing OpenSim musculoskeletal models - Gao, Xiangli; Xu, Datao; Baker, Julien S.; Ee-Chon, Teo; Liang, Minjun; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Dancers represent the primary demographic affected by ankle joint injuries. In certain movements, some Latin dancers prefer landing on the Forefoot (FT), while others prefer landing on the Entire foot (ET). Different stance patterns can have varying impacts on dancers' risk of ankle joint injuries. The purpose of this study is to investigate the differences in lower limb biomechanics between Forefoot (FT) dancers and Entire foot (ET) dancers. Method: A group of 21 FT dancers (mean age 23.50 (S.D. 1.12) years) was compared to a group of 21 ET dancers (mean age 23.33 (S.D. 0.94) years), performing the kicking movements of the Jive in response to the corresponding music. We import data collected from Vicon and force plates into OpenSim to establish musculoskeletal models for computing kinematics, dynamics, muscle forces, and muscle co-activation. Result: In the sagittal plane: ankle angle (0% ~ 100%, p < 0.001), In the coronal plane: ankle angle (0% ~ 9.83%, p = 0.001) (44.34% ~ 79.52%, p = 0.003), (88.56% ~ 100%, p = 0.037), ankle velocity (3.73% ~ 11.65%, p = 0.017) (94.72 ~ 100%, p = 0.031); SPM analysis revealed that FT dancers exhibited significantly smaller muscle force than ET dancers around the ankle joint during the stance phase. Furthermore, FT dancers displayed reduced co-activation compared to ET dancers around the ankle joint during the descending phase, while demonstrating higher co-activation around the knee joint than ET dancers.This study biomechanically demonstrates that in various stance patterns within Latin dance, a reduction in lower limb stance area leads to weakened muscle strength and reduced coactivation around the ankle joint, and results in increased ankle inversion angles and velocities, thereby heightening the risk of ankle sprains. Nevertheless, the increased co-activation around the knee joint in FT dancers may be a compensatory response for reducing the lower limb stance area in order to maintain stability.